2013
DOI: 10.3892/or.2013.2640
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro inhibition of human liver cancer progress by downregulation of the μ-opioid receptor and relevant mechanisms

Abstract: Opiates have long been used as analgesics to relieve pain associated with various medical conditions. μ-opioid receptor (MOR) is the main member of the opioid receptor super-family and the excitation or overexpression of MOR promotes the proliferation of many kinds of tumor cells. It was found in our previous studies that MOR was highly expressed in the tissue and cells of human liver cancer. However, the impact of MOR on the progress of human liver cancer remains unknown. The purpose of this study is to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Recent evidence suggests that opiates have a possible direct effect on lung cancer growth, progression, and epithelial-mesenchymal transition via μ opioid receptor (3133). Similar effect was also observed in hepatocellular carcinoma (34). In accordance, μ-opioid receptor gene (OPRM1) polymorphism has been associated with breast cancer (35) and breast cancer survival (36).…”
Section: Discussionsupporting
confidence: 77%
“…Recent evidence suggests that opiates have a possible direct effect on lung cancer growth, progression, and epithelial-mesenchymal transition via μ opioid receptor (3133). Similar effect was also observed in hepatocellular carcinoma (34). In accordance, μ-opioid receptor gene (OPRM1) polymorphism has been associated with breast cancer (35) and breast cancer survival (36).…”
Section: Discussionsupporting
confidence: 77%
“…MOR1 has been found in a wide range of tumors such as lung carcinoma, breast cancer, prostate cancer, liver cancer, and colon cancer . And MOR1 overexpression has been even reported to be involved in the progression and metastasis of lung cancer and liver cancer . Previous reports studying the expression of MOR1 have observed heterogeneity in subcellular localization of this receptor in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…MOR1 is a major type of opioid receptors, which was shown to be intergral components of a wide variety of human and animal tumor cells in neural and nonneural tissues . It has been found in a wide range of tumors such as lung carcinoma, breast cancer, prostate cancer, liver cancer, and colon cancer . And previous studies have reported on the role of MOR1 in angiogenesis, tumor cell growth, and metastatic spread .…”
Section: Discussionmentioning
confidence: 99%